PELABUHAN PENYEBRANGAN GILIMANUK DI DESA GILIMANUK KECAMATAN MELAYA KABUPATEN JEMBRANA (LINTASAN SEJARAH, DAMPAK SOSIAL EKONOMI DAN EKOLOGI, SERTA POTENSINYA SEBAGAI SUMBER PEMBELAJARAN SEJARAH LOKAL DI SMA) - Duwi Maulida Agistin; Tuty maryati; Desak Made Oka Purnawati (Universitas Pendidikan Ganesha, 2022)
This study aims to determine, 1) The historical trajectory of the establishment of the Gilimanuk ferry port in Gilimanuk Village, Jembrana, Bali, 2) Social, economic, and ecological impacts on the community, 3) Aspects of the existence of the Gilimanuk port which has the potential as a source of historical learning. local in high school. The research method used is a research method with a qualitative descriptive approach including: 1) The research location is at the Gilimanuk Ferry Port, 2) The technique of determining informants is using Purposive Sampling and Snow Ball techniques, 3) Data collection techniques using: observation, interviews, document studies, 4 ) The technique of guaranteeing the authenticity of the data using two techniques, namely: source triangulation and method triangulation, 5) Data analysis techniques consisting of data collection, data reduction, data presentation, verification. The results of this study are: 1) People's ports become a port for crossing goods and people, gradually developing as seen from the dynamics of crossing infrastructure such as the existence of the LCM dock and pontoon dock, and other supporting facilities, 2) The dynamics have an impact on social aspects with the occurrence of attractiveness of the population for sedentary life and the search for economic opportunities around the port, settlement patterns, social and cultural problems, 3) This is interesting and sustainable to be used as a learning resource because there are dynamics of change in every era.